Credit shocks, employment protection, and growth: Firm-level evidence from Spain - Luc Laeven; Peter McAdam; Alexander Popov (European Central Bank (ECB), 2018)
We offer new evidence on the real effects of credit shocks in the presence of employment protection regulations by exploiting a unique provision in Spanish labor laws: dismissal rules are less stringent for Spanish firms with fewer than 50 employees, lowering the cost of hiring new workers. Using a new dataset, we find that during the financial crisis, healthy firms with fewer than 50 employees borrowing from troubled banks grew faster in sectors where capital and labor were sufficiently s ubstitutable. This result does not obtain when we use a different cut-off for Spain or the same cut-off for firms in Germany. Our evidence suggests that labor market flexibility can dampen the negative effect of credit shocks by allowing firms to keep growing by substituting labor for capital.
Keywords: G21; J80; D20; 330; credit crunch; employment protection; capital-labor substitution; firm growth